2010
DOI: 10.1037/a0018486
|View full text |Cite
|
Sign up to set email alerts
|

Attention biases to threat and behavioral inhibition in early childhood shape adolescent social withdrawal.

Abstract: Behavioral inhibition (BI) is a temperament characterized in young children by a heightened sensitivity to novelty, social withdrawal, and anxious behaviors. For many children, these social difficulties dissipate over time. For others, patterns of social withdrawal continue into adolescence. Over time, attention biases to threat may influence the stability of behavioral inhibition and its association with social withdrawal, ultimately modulating the risk for anxiety disorders in BI children. However, we know r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

24
275
6

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 266 publications
(314 citation statements)
references
References 80 publications
24
275
6
Order By: Relevance
“…Results showed that effortful control moderated the association between negative affect and attentional bias, such that low levels of effortful control and high levels of negative affect resulted in bias toward threat. Other work has also shown that cognitive factors (attentional bias toward threat and neural response to novelty) moderate the association between early BI and later anxiety (Perez-Edgar et al 2010;Reeb-Sutherland et al 2009). …”
Section: Temperamentmentioning
confidence: 96%
“…Results showed that effortful control moderated the association between negative affect and attentional bias, such that low levels of effortful control and high levels of negative affect resulted in bias toward threat. Other work has also shown that cognitive factors (attentional bias toward threat and neural response to novelty) moderate the association between early BI and later anxiety (Perez-Edgar et al 2010;Reeb-Sutherland et al 2009). …”
Section: Temperamentmentioning
confidence: 96%
“…Results revealed that anxious children, regardless of disorder, showed an attention bias to threat compared to non-anxious children. Using a similar paradigm, Perez-Edgar et al [32] found that adolescents who were characterized as behaviorally inhibited during early childhood showed increased attention bias to threat compared to noninhibited adolescents. Furthermore, the magnitude of the threat bias was shown to moderate the relation between childhood temperament and maternally reported social withdrawal.…”
Section: Attention To Threat: Behaviormentioning
confidence: 99%
“…In addition, difficulties with attentional control early in development (established experimentally or through observation) have been found to predict stable elevated and low-increasing levels of anxiety across childhood (Duschenne, Vitaro & Tremblay, 2010;Pérez et al, 2010). While ACT was developed to account for the pattern of task performance exhibited by individuals with elevated levels of trait anxiety, extensions of this theoretical framework have implicated impaired attentional control in the genesis of symptoms associated with clinical anxiety disorders, including worry in GAD (Hirsh & Mathews, 2012) and the emergence of specific phobia (Oar et al, 2015).…”
mentioning
confidence: 99%